A Genome-wide Study of Common and Rare Genetic Variants Associated with Circulating Thrombin Activatable Fibrinolysis Inhibitor - Stanne, Tara M.; Olsson, Maja; Lorentzen, Erik; Pedersen, Annie; Gummesson, Anders; Gils, Ann; Jood, Katarina; Engström, Gunnar; Melander, Olle; Declerck, Paul J.; Jern, Christina (Thrombosis and Haemostasis, 2018)
Thrombin-activatable fibrinolysis inhibitor (TAFI) plays a central role in haemostasis, and plasma TAFI concentrations are heritable. Candidate gene studies have identified several variants within the gene encoding TAFI, CPB2, that explain part of the estimated heritability. Here, we describe an exploratory genome-wide association study to identify novel variants within and outside of the CPB2 locus that influence plasma concentrations of intact TAFI and/or the extent of TAFI activation (measured by released TAFI activation peptide, TAFI-AP) amongst 3,260 subjects from Southern Sweden. We also explored the role of rare variants on the HumanExome BeadChip. We confirmed the association with previously reported common variants in CPB2 for both intact TAFI and TAFI-AP, and discovered novel associations with variants in putative CPB2 enhancers. We identified a gene-based association with intact TAFI at CPB2 (PSKAT-O = 2.8 × 10−8), driven by two novel rare nonsynonymous single nucleotide polymorphisms (SNPs; I420N and D177G). Carriers of the rare variant of D177G (rs140446990; MAF 0.2%) had lower intact TAFI and TAFI-AP concentrations compared with non-carriers (intact TAFI, geometric mean 53 vs. 78%, PT-test = 5 × 10−7; TAFI-AP 63 vs. 99%, PT-test = 7.2 × 10−4). For TAFI-AP, we identified a genome-wide significant association at an intergenic region of chromosome 3p14.1 and five gene-based associations (all PSKAT-O < 5 × 10−6). Using well-characterized assays together with a genome-wide association study and a rare-variant approach, we verified CPB2 to be the primary determinant of TAFI concentrations and identified putative secondary loci (candidate variants and genes) associated with intact TAFI and TAFI-AP that require independent validation.
Keywords: thrombin-activatable fibrinolysis inhibitor; fibrinolysis inhibitors; plasma levels; genome-wide association study